STRESS, LAMA TIDUR, LAMA PENGGUNAAN HP DAN HUBUNGANNYA DENGAN DISMENORHOE - Khamidah Achyar; Isnaeni Rofiqoch (Universitas Duta Bangsa Surakarta, 2020)
According to WHO (2010) there are 75% of adolescents who experience menstrual disorders. Based on the results of the study, the prevalence of dysmenorrhoea is 30-60%. The purpose of this research is to analyze the relationship between learning stress, sleep duration, and duration of cell phone use with dysmenorrhea. The analytic research method with cross-sectional design was conducted on 55 students in the Campus of Midwifery Study Program at the Faculty of Health, Muhammadiyah University, Purwokerto in November 2019-January 2020. Data analysis using chi-square. The results of the study, respondents who experienced dysmenorrhea 32 of 55 people (58.18%). There was a significant relationship between learning stress (p = 0.01), sleep duration (p = 0.005) and length of time using Hp (p = 0,000) with dysmenorrhea. Conclusion: Stress of learning, sleep duration and length of cell phone use are associated with dysmenorrhoea